2022
DOI: 10.1111/ajco.13668
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world evidence of cisplatin versus carboplatin in patients with locally advanced nasopharyngeal carcinoma receiving concurrent chemoradiotherapy: A multicenter analysis

Abstract: Background Though concurrent chemoradiotherapy (CCRT) with cisplatin remains a standard of care for patients with locally advanced nasopharyngeal carcinoma (LA‐NPC), carboplatin has alternatively been used without sufficient supportive evidences. Thus, we evaluated an efficacy and tolerability of carboplatin CCRT compared with cisplatin in LA‐NPC patients. Methods Patients with LA‐NPC treated with CCRT were identified through the Thai multicenter head and neck cancer database. Patient tolerability and survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several studies have compared carboplatin alone and cisplatin alone for the chemoradiation of head-and-neck cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Some of these studies were additionally included in one or two meta-analyses from 2016 [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have compared carboplatin alone and cisplatin alone for the chemoradiation of head-and-neck cancer [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. Some of these studies were additionally included in one or two meta-analyses from 2016 [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since radiotherapy of SCCHN has undergone technical improvements during the last 10 years, including the increasing use of high-precision radiotherapy with VMAT (as in the present study), it appears reasonable to take a separate look at studies published more recently. No randomized trials but several retrospective studies were identified that were published between 2017 and 2023 [ 37 , 38 , 39 , 40 , 41 ]. Three of these studies found that chemoradiation with carboplatin was similarly effective as cisplatin-based treatment [ 37 , 38 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations